An Investigation of Psychological Factors Inluencing Investment Decision Making - Chang, Hsin Hue (The Indonesian Capital Market Review, 2010)
This study applies a second-order conirmatory factor analysis (CFA) approach to investigate psychological factors inluencing individuals' investment decision-making. A second-order CFA approach consists of ive irst-order psychological factors in terms of mental accounting, regret avoidance, self-control, heuristic and overconidence, and one second-order factor in terms of investment decision-making. Quantitative data was yielded by the questionnaire, and an effective sample of 752 responses was used to execute the estimation procedure. The results reveal that there exist statistically signiicant relationships between ive psychological factors and investment decision-making. Investors are likely to consider a product with different functions as one with different mental accounts (gains). Thus, inancial institutions are advised to provide their potential customers with multi-function products. Since self-control is a signiicant self-imposed mechanism for investment decision-making, inancial institutions can merchandise products that can help their customers to execute the self-imposed rules of thumb.